2019
DOI: 10.1016/j.jaci.2018.10.067
|View full text |Cite
|
Sign up to set email alerts
|

Fibrostenotic eosinophilic esophagitis might reflect epithelial lysyl oxidase induction by fibroblast-derived TNF-α

Abstract: (to K.A.W. and H.N.). J.M.S. is funded by the Stuart Starr Endowed Chair, Food Allergy Research and Education. J.M.S. and A.B.M. are funded in part by the Consortium of Eosinophilic Gastrointestinal Disease Researchers (CEGIR). CEGIR (U54 AI117804) is part of the Rare Diseases Clinical Research Network (RDCRN), an initiative of the Office of Rare Diseases Research (ORDR), National Center for Advancing Translational Sciences (NCATS), and is funded through collaboration between the National Institute of Allergy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 59 publications
1
33
0
Order By: Relevance
“…Major cytokines involved in the pathogenesis of eosinophilic esophagitis such as IL‐4, IL‐5, IL‐13, and TNF have been tested for the treatment of eosinophilic esophagitits 133 . Along with Th2 cytokines, TGF‐β is the major cytokine that mediates lamina propria remodeling in eosinophilic esophagitis 134 . Recently, it has been reported that TGF‐β alters esophageal epithelial barrier function via claudin‐7 135 .…”
Section: Tight Junction In Eosinophilic Esophagitismentioning
confidence: 99%
“…Major cytokines involved in the pathogenesis of eosinophilic esophagitis such as IL‐4, IL‐5, IL‐13, and TNF have been tested for the treatment of eosinophilic esophagitits 133 . Along with Th2 cytokines, TGF‐β is the major cytokine that mediates lamina propria remodeling in eosinophilic esophagitis 134 . Recently, it has been reported that TGF‐β alters esophageal epithelial barrier function via claudin‐7 135 .…”
Section: Tight Junction In Eosinophilic Esophagitismentioning
confidence: 99%
“…Here we provide an example of such an experiment by treating normal esophageal organoids with interleukin 13 (IL-13) to model reactive changes induced in esophageal epithelium by eosinophils; however, any bioactive compounds (cytokines, antibodies, small molecule inhibitors) can be utilized to model pathologic conditions and/or treatment strategies. Representative images of esophageal organoids treated with IL-13, as well as gene expression profiles of select EoE-relevant genes (Blanchard et al, 2007;Kasagi et al, 2019), can be found in Figure 2.…”
Section: Modeling Of Reactive Epithelium In Esophageal Organoidsmentioning
confidence: 99%
“…In this issue of the Journal, Kasagi et al 8 provide evidence that the enzyme lysyl oxidase (LOC, protein product of LOX), which promotes formation of extracellular collagen fibers, can serve as a biomarker for fibrostenotic disease in patients with EoE. Previous publications revealed that LOX expression was upregulated in biopsy specimens from patients with EoE and in an epithelial cell line.…”
mentioning
confidence: 99%
“…Previous publications revealed that LOX expression was upregulated in biopsy specimens from patients with EoE and in an epithelial cell line. 9,10 Kasagi et al 8 found that LOX expression correlated with clinical and endoscopic fibrostenotic disease. This upregulation was linked to epithelial cells stimulated by TNF-a produced by fibroblasts.…”
mentioning
confidence: 99%
See 1 more Smart Citation